An Approach for Cross-Domain Optimization for Automated Adaptation Design of Mechatronic Systems - Behringer, Marc; Götz, Stefan; Wartzack, Sandro (DS 133: Proceedings of the 35th Symposium Design for X (DFX2024), 2024)
The product development of mechatronic systems remains complicated as interdisciplinary system interrelations and divergent requirements from the involved engineering domains must be taken into account. Thus, the inherent complexity and interdependencies of mechatronic systems usually require an iterative procedure to generate an optimized product even for small design adaptations. Therefore, the proposed approach aims to automate subprocesses in the adaptation design of mechatronic systems from the problem identification to the optimized product. It involves a cross-domain optimization by utilizing the knowledge from previous product development cycles and optimization histories. The approach is demonstrated using an electronic window regulator as an exampl
Keywords: Adaptation Design; Mechatronic Systems; Knowledge-Based Engineering; Optimization; Systems Engineering